2023
DOI: 10.7717/peerj.15459
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gene expressions of Caco-2 cell responses to LPS and ploy(I:C) stimulation

Abstract: The intestinal epithelium barrier serves as a highly dynamic immunologic frontier in the defense against invading pathogenic bacteria and viruses. Hence, understanding of the complicated underlying relationship between enteric pathogens and the intestinal epithelium barrier is vital for developing strategies to improve the intestinal health of farm animals. To this end, Caco-2 cells were stimulated by 1 µg/ml lipopolysaccharide (LPS) for 24 h and 5 µg/ml polyinosinic-polycytidylic acid (ploy(I:C)) for 4 h to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In our experiments, we observed that S. typhimurium infection determined a decrease in TGFB1 expression in IPEC-J2 cells. This is not surprising, considering a recent study by Qin et al [90], who mimed the bacterial infection process with an LPS stimulus in human Caco-2 colon cells. The authors observed a down-regulation of several genes involved in the inflammation response linked to TGF-beta signaling pathways.…”
Section: Discussionmentioning
confidence: 87%
“…In our experiments, we observed that S. typhimurium infection determined a decrease in TGFB1 expression in IPEC-J2 cells. This is not surprising, considering a recent study by Qin et al [90], who mimed the bacterial infection process with an LPS stimulus in human Caco-2 colon cells. The authors observed a down-regulation of several genes involved in the inflammation response linked to TGF-beta signaling pathways.…”
Section: Discussionmentioning
confidence: 87%